2021
DOI: 10.5296/bms.v12i1.18395
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Specificities of Succession’ Failure and Success in the Context of Unlisted Moroccan Family-Owned Businesses

Abstract: The purpose of this research aims to study the relationship between the cultural specificities of the Moroccan context and the success or failure of succession strategies (in terms of planning and process) in the case of Moroccan unlisted family businesses. Our study covered a sample of 20 unlisted Moroccan family businesses, 8 of which are SMEs, 6 are large firms, and 6 are VSEs, through a qualitative research based on semi-structured interviews with the managers of family businesses. Our results explain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Our results correspond to the statements of Filser et al (2013) and Gagnè et al (2011). Allioui et al (2021) argued that it is the timely planning of a generational change that can help to ensure a smooth transition of ownership. The reason for the reluctance of the owner to leave the business was considered to be that the owners could not disengage from the family business because they did not have time to perform hobbies in addition to their daily work.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Our results correspond to the statements of Filser et al (2013) and Gagnè et al (2011). Allioui et al (2021) argued that it is the timely planning of a generational change that can help to ensure a smooth transition of ownership. The reason for the reluctance of the owner to leave the business was considered to be that the owners could not disengage from the family business because they did not have time to perform hobbies in addition to their daily work.…”
supporting
confidence: 88%
“…We found that the owners of Slovak family businesses focused on topics that also correspond to the world literature in the field of succession (Duh 2014;Zellweger et al 2019;B ąkiewicz 2020;Allioui et al 2021;Kandade et al 2021). What makes our research exceptional is that we focused the main part on the importance of individual expressions in the conditions of Slovak family businesses.…”
mentioning
confidence: 63%
See 1 more Smart Citation